Ahakoa he kiri mā : a fire in our blood : a thesis presented in partial fulfilment of the requirements for a Master of Arts, Psychology at Massey University, Palmerston North, New Zealand - Roestenburg, Michelle Waireti Maria (Massey University, 2010)
This study approaches the nexus of whakapapa, Māori ethnic identity and non-conventional presentations of Māoriness. The factors and forces that enable or disable positive Māori identity development are examined through the experiences and meanings of six Māori women who are strongly and positively identified as Māori yet unidentifiable as Māori in appearance. By privileging kaupapa Māori research methodology, Māori participants and researcher, within mātauranga and tikanga Māori, a research paradigm capable of congruent cultural interpretation of Māori identity was developed. After the conversations were transcribed, close reading of the transcript identified and critiqued factors and forces that indicated either ‘tangibly sheltering’ identity development environments of mana Māori that were incongruent with wider societal positioning of Māori, or ‘tangibly traumatising’ environments that denigrated Māori and mirrored societal attitudes to Māori. Contemporary and historical socio-political colonial influences articulated with Māori-centric forces. Whānaungātanga or collectivity as an outcome of tikanga or the tipuna inspired desire to seek what is right and good at the intra-personal and inter-subjective levels was revealed as the indomitable heart force of Māori identity. A felt and embodied connection to ancestors led the participants deeper into who they were as Māori women, this presence and pulse was either enhanced by, or continued in spite of socio-political forces. A comparative focus on ‘Māori dignity’ revealed a rigid incapacity in New Zealand society generally and the ‘helping professions’ particularly, to move beyond an artificially entrenched ‘Māori deficit’ position. What is powerful and distinct about Māori is ignored when history and holisim are disallowed. Holistic and historical reconnection are indicated for Māori and Non-Māori to make existential sense of current day Māori and Non-Māori realities and to move out of a fixation on the outcomes of colonisation without attention to cause. Implications for the re-emergence of collaboratively intelligent ways to critique the existing and imminent flows of power within and without Te Ao Māori are discussed for the restoration of dignity to Māori and Non-Māori identities.
Keywords: Maori identity; Ethnic identity; Psychology; Tipuna; Matauranga Maori; Kaupapa Maori; White domination; Hegemony; Tino rangatiratanga; Indigenous sovereignty